PERANAN GURU PAI DALAM MENGEVALUASI HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK ANAK BERKEBUTUHAN KHUSUS DI SLB DARUL ULUM JOGOROTO JOMBANG - Putri Ainul Maulida; Iva Inayatul Ilahiyah (Kampus Akademik Publiser, 2024)
Islamic Religious Education can be defined as learning that is carried out both in terms of academic content and daily practice, by individuals or educational institutions that provide material about Islam to those who want to learn it. One of them is in SLB Darul Ulum Jogoroto Jombang, which consists of several levels starting from elementary school, junior high school and vocational school which are located in one location. This school is specifically for children with special needs to get educational services that are in accordance with their specialities to support the growth and development of ABK (Children with Special Needs).The research results show that: 1) The role of PAI teachers in children with special needs in SLB Darul Ulum Jogoroto Jombang, namely: Teachers as educators, mentors, teachers, motivators, and evaluators. 2) While the Role of PAI Teachers in Evaluating Learning Outcomes, namely: The role of the teacher as an evaluator is to carry out everything from the evaluation planning stage, the implementation of the evaluation, to the utilisation of the evaluation results/follow-up. Evaluation results can be used by teachers to obtain important information to be a reference for future follow-up activities. 3) The factors that influence PAI Teachers in Evaluating Learning Outcomes in Islamic Religious Education Subjects for Children with Special Needs at Darul Ulum Jogoroto Jombang Special School, including: a. Supporting factors: Family factors; Teacher's approach to children with special needs for the success of the learning outcomes achieved. Inhibiting factors: Time limitation factors; Environmental factors that do not support.